Composition for trivalent chromium black chemical conversion treatment and method for manufacturing member provided with chemical conversion coating film
By using a specific ratio of vanadium-containing and hydroxycarboxylic acid compositions with trivalent chromium, organosulfur compounds, and organophosphonic acid compounds for chemical conversion treatment, the problems of black appearance and corrosion resistance caused by the increase in cumulative treatment area were solved, achieving stable chemical conversion coating formation and quality control.
Patent Information
- Application Number
- CN202480035619.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-01
- Filing Date
- 2024-04-02
- Publication Date
- 2025-12-23
AI Technical Summary
Existing chemical conversion treatment compositions struggle to maintain both a black appearance and high corrosion resistance as the cumulative treated area increases, and existing addition methods have failed to effectively address this issue.
A chemical conversion treatment composition that does not contain hexavalent chromium is formed by combining vanadium-containing substances and hydroxycarboxylic acid-containing substances in a specific ratio. The composition contains trivalent chromium, organosulfur compounds, organophosphonic acid compounds and other auxiliary components. The stability and performance of the composition are ensured through quantitative replenishment management.
Even with increased cumulative treatment area under quantitative replenishment management, a chemical conversion coating with a stable black appearance and excellent corrosion resistance can be formed, achieving quality stabilization in mass production.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a chemical conversion treatment composition which is substantially free of hexavalent chromium ions, i.e., hexavalent chromium-free, can form a black film containing trivalent chromium on a metal surface of a member, and can maintain stable performance and long bath life even when operated in a quantitative replenishment mode, and a method for producing a member having a chemical conversion film formed by the above chemical conversion treatment composition. BACKGROUND
[0002] In recent years, in accordance with directives such as the RoHS (Restriction of the Use of Certain Hazardous Substances in Electrical and Electronic Equipment) directive, the ELV (End of Life Vehicles) directive, and the like, which take the environment into consideration, the use of harmful substances (lead, mercury, cadmium, hexavalent chromium ions, and the like) is required to be limited.
[0003] In response to this trend, as a chemical conversion film effective as an anticorrosion film for members having a metal surface such as a zinc-plated member, a chromate film in which a composition for forming a chemical conversion film by chemical conversion treatment (hereinafter, this composition is referred to as a "chemical conversion treatment composition") used in the past has been changed from a chromate containing hexavalent chromium ions to a chemical conversion treatment composition containing trivalent chromium ions.
[0004] Among the chemical conversion treatment compositions, there is a composition capable of forming a chemical conversion film having a black appearance (hereinafter, this chemical conversion film is referred to as a "black film") which is widely used for members (press-molded products such as panels, housings, hinges, and face plates), parts (fastening parts such as bolts and nuts, fixtures, and the like), and the like of office equipment, electrical equipment, and the like, but there is a problem in that the stability of the chemical conversion treatment composition decreases, and there is a problem in that as the cumulative amount of the treatment area (hereinafter, simply referred to as the "cumulative treatment area") of members and the like treated with the chemical conversion treatment composition increases, the appearance of the black film deteriorates, i.e., the black appearance cannot be obtained and becomes gray.
[0005] In order to solve the problem of reduced stability, for example, as shown in Patent Document 1, a method of adding two specific organic acids or salts thereof is proposed to seek stability. In order to solve the problem of appearance deterioration of the black coating film due to an increase in the cumulative processing area, for example, as shown in Patent Document 2, a method of adding a sulfur compound as an organic substance and an organic phosphonic acid compound selected from one or two or more of the group consisting of organic phosphonic acids and ions and salts thereof is proposed.
[0006] Prior Art Documents
[0007] Patent Documents
[0008] Patent Document 1: Japanese Patent No. 6532003
[0009] Patent Document 2: Japanese Patent No. 4840790 SUMMARY
[0010] Problems to be Solved by the Invention
[0011] However, the present inventors and others have found, as a result of research, that the method of adding two specific organic acids or salts thereof as in Patent Document 1 cannot take into account both appearance deterioration due to an increase in the cumulative processing area and high corrosion resistance. Also, as in the method of adding a sulfur compound as an organic substance and an organic phosphonic acid compound as in Patent Document 2, it has been confirmed that, in order to maintain a good black appearance and high corrosion resistance, it is preferable to increase the amount of addition of the above-mentioned compounds as the cumulative processing area increases. That is, it has been confirmed that the method of Patent Document 2 has room for improvement in terms of suitability for quantitative replenishment management that assumes continuous processing.
[0012] Therefore, the object of the present invention is to provide a chemical conversion treatment composition that forms a chemical conversion coating film that has both a black appearance and high corrosion resistance even when the cumulative processing area increases under quantitative replenishment management, and a method of manufacturing a member provided with the chemical conversion coating film.
[0013] Solution to the Problem
[0014] In order to solve the above-mentioned problem, the present inventors have conducted intensive research. As a result, the following recognition was obtained: by containing a vanadium-containing substance and a hydroxyl carboxylic acid-containing substance in a specific ratio, a chemical conversion treatment composition that forms a chemical conversion coating film that has both a black appearance and high corrosion resistance even when the cumulative processing area increases under quantitative replenishment management can be obtained.
[0015] The present invention based on the above insight provides, as one solution, a chemical conversion treatment composition that contains a trivalent chromium-containing substance, an organic sulfur compound, an organic phosphonic acid compound, a vanadium-containing substance, and a hydroxyl carboxylic acid-containing substance.
[0016] In the above-mentioned chemical conversion treatment composition, the ratio of the molar concentration of the vanadium-containing substance in terms of vanadium to the molar concentration of the hydroxycarboxylic acid-containing substance in terms of hydroxycarboxylic acid can be 1:1 to 1:10.
[0017] In the above-mentioned chemical conversion treatment composition, the content of the trivalent chromium-containing substance can be 1 to 10 g / L in terms of chromium, the content of the organic sulfur compound can be 0.1 to 10 g / L, and the content of the organic phosphonic acid compound can be 0.1 to 20 g / L.
[0018] The above-mentioned chemical conversion treatment composition can contain one or more selected from the group consisting of a nickel-containing substance and a cobalt-containing substance.
[0019] The above-mentioned chemical conversion treatment composition can contain a zinc-containing substance in an amount of 15 g / L or less in terms of zinc.
[0020] In the present invention, as another aspect, there is provided a method for producing a member provided with a chemical conversion coating, which includes bringing the above-mentioned chemical conversion treatment composition into contact with a substrate having a surface of a zinc-containing material. The chemical conversion treatment composition is preferably managed by quantitative replenishment.
[0021] Effects of the Invention
[0022] When the above-mentioned chemical conversion treatment composition of the invention is used, even if the cumulative treatment area increases under quantitative replenishment management, a black coating having a black appearance and excellent corrosion resistance can be stably formed. Therefore, compared with the prior art, the chemical conversion treatment composition of the invention can stabilize the quality by simple management (quantitative replenishment), and thus greatly contributes to the stabilization of quality in mass production. DETAILED DESCRIPTION
[0023] The chemical conversion treatment composition of one embodiment of the invention contains a trivalent chromium-containing substance, an organic sulfur compound, an organic phosphonic acid compound, a vanadium-containing substance, and a hydroxycarboxylic acid-containing substance, the ratio of the molar concentration of the vanadium-containing substance in terms of vanadium to the molar concentration of the hydroxycarboxylic acid-containing substance in terms of hydroxycarboxylic acid is 1:1 to 1:10, and it is an aqueous composition substantially containing no hexavalent chromium ions, i.e., a hexavalent chromium-free composition.
[0024] By subjecting a member having a surface formed of a metal-based material such as zinc plating to treatment of bringing it into contact with the chemical conversion treatment composition of the embodiment, a chemical conversion coating having a black appearance and high corrosion resistance can be formed. Moreover, even if the cumulative treatment area increases under quantitative replenishment management, the performance is difficult to change, and thus the quality can be stabilized by simple management (quantitative replenishment).
[0025] Hereinafter, each component will be described in detail.
[0026] (1) Substance containing trivalent chromium
[0027] The chemical conversion treatment composition of the present embodiment contains a substance containing trivalent chromium. The substance containing trivalent chromium is composed of one or two or more selected from the group consisting of trivalent chromium and a water-soluble substance containing trivalent chromium (examples of which include trivalent chromium complexes). As a raw material substance of the substance containing trivalent chromium, a compound that can generate the substance containing trivalent chromium in water (hereinafter referred to as "trivalent chromium compound") is preferably used.
[0028] Examples of the trivalent chromium compound include trivalent chromium salts such as chromium chloride, chromium sulfate, chromium nitrate, chromium phosphate, and chromium acetate, and a compound obtained by reducing a hexavalent chromium compound such as chromic acid or dichromate to trivalent chromium using a reducing agent. The trivalent chromium compound can be composed of only one kind of compound, or can be composed of a plurality of kinds. Examples of the preferable trivalent chromium compound are chromium nitrate and chromium chloride. Note that since the chemical conversion treatment composition of the present application does not actively add a hexavalent chromium compound as a raw material, the chemical conversion treatment composition of the present application does not substantially contain hexavalent chromium, i.e., is so-called hexavalent chromium-free.
[0029] From the viewpoint of stably forming a chemical conversion coating, the content of the substance containing trivalent chromium is preferably set to 1 g / L or more in terms of chromium. The upper limit of the content of the substance containing trivalent chromium is not particularly limited, but from the viewpoint of appropriately securing the effect of containing the substance containing trivalent chromium and not increasing the load of waste liquid treatment, the upper limit is preferably set to about 10 g / L. Further, from the viewpoint of easily forming a chemical conversion coating, the content of the substance containing trivalent chromium is more preferably set to 2 to 5 g / L.
[0030] (2) Organic sulfur compound
[0031] The chemical conversion treatment composition of the present embodiment contains an organic compound containing sulfur among its constituent elements, i.e., an organic sulfur compound. As the sulfur-containing functional group contained in the organic sulfur compound, examples include -SH (mercapto group), -S- (sulfide group), >C=S (thioaldehyde group, thio ketone group), -COSH (thiocarbonyl group), -CSSH (dithiocarbonyl group), -CSNH2 (thioamide group), -SCN (thiocyanate group, isothiocyanate group). As specific examples of the organic sulfur compound, the following can be listed: ammonium thiolactate, thiolactic acid, thiomaleic acid, thioacetamide, dithiolactic acid, ammonium dithiolactate, ammonium dithiodilactate, dithiodilactate, cystine, saccharin, thiamine nitrate, sodium N,N-diethyldithiocarbamate, 1,3-diethyl-2-thiourea, bipyridine, N-thiazole-2-sulfonamide, 1,2,3-benzotriazole, 2-thiazoline-2-thiol, thiazole, thiourea, thiozole, sodium thio-3-hydroxyindole-2-carboxylic acid, o-sulfonamidobenzoic acid, sulfanilic acid, orange II, methyl orange, naphthylamine sulfonic acid, naphthalene-α-sulfonic acid, 2-mercaptobenzothiazole, 1-naphthol-4-sulfonic acid, Schaeffer acid, sulfadiazine, ammonium thiocyanate, potassium thiocyanate, sodium thiocyanate, rhodanine, ammonium sulfide, sodium sulfide, ammonium sulfate, thio-glycerol, thioacetic acid, potassium thioacetate, dithio-glycolic acid, 3,3-thiodipropionic acid, and aminothiourea.
[0032] Among these organic sulfur compounds, from the viewpoint of stably obtaining a black-colored film, it is preferable to contain one or two or more selected from the group consisting of thiolactic acid and dithiodilactate, and ions and salts thereof.
[0033] The organic sulfur compound is considered to be one of the components that directly affect the blackening of the chemical conversion film, and its content is preferably 0.1 to 10 g / L. If its content is less than 0.1 g / L, the blackening is weak, and even if it is added in excess of 10 g / L, the effect of blackening is saturated. From the viewpoint of appropriately ensuring the effect of containing the organic sulfur compound and stably forming a black-colored film, the content of the organic sulfur compound is more preferably 0.3 to 8 g / L, and particularly preferably 0.5 to 6 g / L.
[0034] (3) Organic phosphonic acid compound
[0035] The "organic phosphonic acid compound" of the present embodiment refers to a substance composed of one or more selected from the group consisting of organic phosphonic acids and ions and salts thereof. Here, the "organic phosphonic acid" refers to a substance having the general formula R-P(=O)(OH)2 (R is an organic group) and having an organic group bonded to a phosphonic acid group. As the organic phosphonic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, 2-phosphonobutane-1,2,4-tricarboxylic acid, amino tri(methylene phosphonic acid), ethylenediamine tetra(methylene phosphonic acid), and diethylenetriamine penta(methylene phosphonic acid) can be exemplified. As the salts of these organic phosphonic acids, tetrasodium salt of 1-hydroxyethylidene-1,1-diphosphonic acid, trisodium salt of 1-hydroxyethylidene-1,1-diphosphonic acid, penta sodium salt of ethylenediamine tetra(methylene phosphonic acid), and hepta sodium salt of diethylenetriamine penta(methylene phosphonic acid) can be exemplified. These salts are mostly in a state of dissociation of sodium ions in the chemical conversion treatment composition.
[0036] The content of the organic phosphonic acid compound is preferably 0.1 to 20 g / L. If the content is less than 0.1 g / L, the chemical conversion coating is likely to be insufficiently formed, and even if it exceeds 20 g / L, the formation of the chemical conversion coating is likely to be saturated. From the viewpoint of appropriately ensuring the effect of containing the organic phosphonic acid compound and stably forming the chemical conversion coating, the content of the organic phosphonic acid compound is more preferably 0.2 to 15 g / L, and particularly preferably 0.3 to 10 g / L.
[0037] (4) Vanadium-containing substance
[0038] The chemical conversion treatment composition of the present embodiment contains a vanadium-containing substance. The vanadium-containing substance is composed of one or two or more selected from the group consisting of water-soluble vanadium-containing substances, and contains vanadium ions and complexes thereof, and vanadate ions and other oxoacid ions of vanadium. As the raw material substance of the vanadium-containing substance, a compound capable of generating a vanadium-containing substance in water (hereinafter referred to as "vanadium compound") is preferably used.
[0039] Exemplary vanadium compounds include vanadium chloride, vanadium sulfate, vanadyl sulfate, sodium vanadate, potassium vanadate, vanadium (II) oxide, and vanadium (V) oxide. The vanadium compound can be composed of only one compound, or can be composed of a plurality of kinds.
[0040] The molar concentration of the vanadium-containing substance is preferably 0.001 mol / L or more and 1 mol / L or less in terms of vanadium. If the above molar concentration is less than 0.001 mol / L, it is sometimes difficult to obtain a chemical conversion coating having a black appearance, and if it exceeds 1 mol / L, the stability of the chemical conversion treatment composition sometimes shows a tendency to decrease. From the viewpoint of ensuring the stability of the chemical conversion treatment composition and obtaining a good chemical conversion coating, the molar concentration of the vanadium-containing substance in terms of vanadium is sometimes more preferably 0.002 to 0.5 mol / L, and sometimes particularly preferably 0.005 to 0.1 mol / L.
[0041] (5) Hydroxyl group-containing carboxylic acid-containing substance
[0042] The chemical conversion treatment composition of the present embodiment contains a hydroxyl group-containing carboxylic acid-containing substance. In the present specification, the hydroxyl group-containing carboxylic acid-containing substance is composed of one or two or more selected from the group consisting of a hydroxyl group-containing carboxylic acid which is a carboxylic acid having a hydroxyl group, and a water-soluble substance containing the hydroxyl group-containing carboxylic acid-containing substance. As a raw material substance of the hydroxyl group-containing carboxylic acid-containing substance, a water-soluble compound which can be dissolved in water and generate a hydroxyl group-containing carboxylic acid-containing substance (hereinafter referred to as "water-soluble hydroxyl group-containing carboxylic acid compound") is preferably used. The water-soluble hydroxyl group-containing carboxylic acid compound also includes esters which can generate a hydroxyl group-containing carboxylic acid by hydrolysis.
[0043] As the hydroxyl group-containing carboxylic acid, one-hydroxy monobasic carboxylic acids such as glycolic acid, lactic acid, and the like; one-hydroxy polybasic carboxylic acids such as malic acid, citric acid, and the like; polyhydroxy monobasic carboxylic acids such as ascorbic acid, and the like; polyhydroxy polybasic carboxylic acids such as tartaric acid, and the like, and the like can be exemplified, but are not limited to these. The water-soluble hydroxyl group-containing carboxylic acid compound also includes salts such as sodium salts, potassium salts, and the like, and ions of these hydroxyl group-containing carboxylic acids.
[0044] The molar concentration of the hydroxyl group-containing carboxylic acid-containing substance is preferably set to 0.001 mol / L or more and 5 mol / L or less in terms of the hydroxyl group-containing carboxylic acid. If the above molar concentration is less than 0.001 mol / L, the stability of the chemical conversion treatment composition sometimes shows a tendency to decrease, and if it exceeds 5 mol / L, the load sometimes increases when the chemical conversion treatment composition is discharged. From the viewpoint of appropriately ensuring the stability and the drainage property of the chemical conversion treatment composition, the molar concentration of the hydroxyl group-containing carboxylic acid-containing substance in terms of the hydroxyl group-containing carboxylic acid is sometimes more preferably 0.002 to 5 mol / L, and is sometimes particularly preferably 0.005 to 1 mol / L.
[0045] In the chemical conversion treatment composition of the present embodiment, the ratio of the molar concentration of the vanadium-containing substance in terms of vanadium to the molar concentration of the hydroxyl group-containing carboxylic acid-containing substance in terms of the hydroxyl group-containing carboxylic acid is 1:1 to 1:10. By adjusting the molar concentration of the vanadium-containing substance and the molar concentration of the hydroxyl group-containing carboxylic acid-containing substance within the above range, even if the cumulative treatment area increases, a chemical conversion coating having a black appearance and high corrosion resistance can be stably obtained.
[0046] (6) Nickel-containing substance, cobalt-containing substance
[0047] The chemical conversion treatment composition of the present embodiment can contain one or more selected from the group consisting of a nickel-containing substance and a cobalt-containing substance. The nickel-containing substance is composed of one or two or more selected from the group consisting of water-soluble nickel-containing substances, and contains nickel ions and complexes thereof. The cobalt-containing substance is composed of one or two or more selected from the group consisting of water-soluble cobalt-containing substances, and contains cobalt ions and complexes thereof. The nickel-containing substance contributes to blackening, and the cobalt-containing substance contributes to improvement in corrosion resistance. As the raw material substance of the nickel-containing substance and the cobalt-containing substance, a compound (nickel compound, cobalt compound) that generates the nickel-containing substance and the cobalt-containing substance in water is desirably used.
[0048] Examples of the nickel compound include nickel chloride, nickel sulfate, nickel nitrate, nickel phosphate, and nickel acetate. The nickel compound can be composed of only one compound, or can be composed of a plurality of kinds. Examples of the cobalt compound include cobalt chloride, cobalt sulfate, cobalt nitrate, cobalt phosphate, and cobalt acetate. The cobalt compound can be composed of only one compound, or can be composed of a plurality of kinds.
[0049] In the case where the nickel-containing substance is contained, the content thereof is preferably 0.05 to 5 g / L in terms of nickel. If the content is less than 0.05 g / L, it is sometimes difficult to obtain the effect of improvement in blackening, and if it exceeds 5 g / L, the corrosion resistance is sometimes reduced. From the viewpoint of suppressing the influence on the corrosion resistance and stably obtaining the effect of blackening, the content of the nickel-containing substance in terms of nickel is sometimes preferably 0.1 to 3 g / L. In the case where the cobalt-containing substance is contained, the content thereof is preferably 0.05 to 5 g / L in terms of cobalt. If the content is less than 0.05 g / L, it is sometimes difficult to obtain the effect of improvement in corrosion resistance, and if it exceeds 5 g / L, the corrosion resistance is sometimes reduced. From the viewpoint of stably obtaining the effect of improvement in corrosion resistance, the content of the cobalt-containing substance in terms of cobalt is sometimes preferably 0.1 to 3 g / L.
[0050] (7) Other components
[0051] The chemical conversion treatment composition of the present embodiment can contain one or more selected from the group consisting of metal ions, inorganic acids and anions thereof, inorganic colloids, silane coupling agents, nitrogen compounds, and fluorine compounds, in addition to the above-mentioned substances. Furthermore, one or more selected from the group consisting of polymers such as waxes, corrosion inhibitors, surfactants, plasticizing dispersants, coloring agents such as dyes and pigments, drying agents, and dispersants can be further contained. Furthermore, a reducing substance can be simultaneously added.
[0052] As the metal ions, ions of Na, K, Ag, Au, Ru, Nb, Ta, Pt, Pd, Fe, Ca, Mg, Zr, Sc, Ti, Mn, Cu, Zn, Sn, Y, Mo, Hf, Te, and W can be exemplified, and they can also exist in the form of oxyacid ions. Note that in the case where the member (base material) to be subjected to chemical conversion treatment has a surface of a material containing zinc, as the cumulative treatment area increases, a zinc-containing substance (specifically, zinc ions, complexes thereof, etc.) as a zinc-containing water-soluble substance can be accumulated in the chemical conversion treatment composition. In general, when the zinc-conversion concentration of the zinc-containing substance in the chemical conversion treatment composition increases, it is difficult to maintain the black appearance of the chemical conversion coating, but in the chemical conversion treatment composition of the present embodiment, even if the zinc-conversion content of the zinc-containing substance is 15 g / L, a black appearance can be obtained, and thus the zinc-containing substance can be contained within this range (15 g / L or less).
[0053] As the inorganic acid, hydrochloric acid, hydrogen fluoride acid, hydrogen bromic acid, and the like, halogenated hydrogen acids, chloric acid, perchloric acid, chlorous acid, hypochlorous acid, sulfuric acid, sulfurous acid, nitric acid, and nitrous acid can be exemplified, and inorganic acids containing phosphorus such as phosphoric acid (orthophosphoric acid), polyphosphoric acid, metaphosphoric acid, pyrophosphoric acid, superphosphoric acid, hypophosphoric acid, and perphosphoric acid can also be contained. The inorganic acid can also be contained in the chemical conversion treatment composition in the form of ions.
[0054] The molar concentration of these inorganic acids and / or ions thereof in the chemical conversion treatment composition is not particularly limited. The ratio of the total molar concentration of the inorganic acid and the ion thereof to the total molar concentration of the trivalent chromium ions and the above-described metal ions (including vanadium ions, nickel ions, cobalt ions, etc.) is sometimes preferably 0.1 to 10, and more preferably 0.5 to 3.
[0055] As the inorganic colloid, silica sol, alumina sol, titania sol, and zirconia sol can be exemplified, and as the silane coupling agent, an organosilane coupling agent such as vinyltriethoxysilane can be exemplified.
[0056] Among the nitrogen compounds, heterocyclic compounds, ureas, aliphatic amines, acid amides, aminocarboxylic acids, ammonium salt ureas, amines, nitrobenzenesulfonic acids, and the like can be exemplified, and urea, ammonium salt, nitrate, and the like can be exemplified as the nitrogen compounds, and the preferable content thereof is 0.5 to 50 g / L alone.
[0057] (8) Solvent
[0058] The solvent of the chemical conversion treatment composition of the present embodiment is mainly water, and from the viewpoint of stabilizing the contained components, an organic solvent that is soluble in water such as an alcohol, an ether, and an ester can also be mixed. The proportion of the organic solvent in the total solvent is not particularly limited, but from the viewpoint of ensuring appropriate drainage treatment properties, it is sometimes preferably 10% by mass or less.
[0059] (9) pH
[0060] The pH of the chemical conversion treatment composition of the present embodiment is not particularly limited as long as it is acidic, but is preferably in the range of pH 1 to 4, and particularly preferably pH 2 to 3 from the viewpoint of stability of the chemical conversion treatment composition. The pH adjustment can be performed using an alkaline substance such as sodium hydroxide, sodium bicarbonate, ammonia, or an acidic substance such as hydrochloric acid, nitric acid, sulfuric acid.
[0061] (10) Upper layer coating
[0062] After the chemical conversion treatment using the chemical conversion treatment composition of the present embodiment, water washing is performed, and inorganic, organic, or organic-inorganic composite coating is performed before or after drying, whereby the corrosion resistance can be further improved. As the inorganic upper layer coating, a silica-based upper layer coating, a phosphoric acid-based upper layer coating, and the like can be given, and other upper layer coatings are also possible. As the organic upper layer coating, there is no limitation on the paint or the resin, and it can be water-based or non-water-based. Organic coating films such as polyethylene, polyvinyl chloride, polystyrene, polypropylene, acrylic resin, methacrylic resin, polycarbonate, polyamide, polyacetal, fluororesin, urea-formaldehyde resin, phenol-formaldehyde resin, unsaturated polyester resin, polyurethane, alkyd resin, epoxy resin, melamine resin, and the like can be given, but are not limited to these. The timing of performing the upper layer coating can be immediately after drying after the chemical conversion treatment, or can be after secondary processing such as bending or molding, and the number of times of upper layer coating is also not limited. The method of the upper layer coating is also not particularly limited, and various methods such as painting, dip coating, electrostatic coating, electrophoretic coating, and powder coating can be used.
[0063] (11) Substrate
[0064] The member (substrate) to be subjected to the chemical conversion treatment is not limited in terms of the material as long as it can be appropriately subjected to the chemical conversion treatment by the chemical conversion treatment composition of the present embodiment. As an example of the substrate, a substrate having a surface of a material containing zinc can be given, and as a specific example of such a substrate, a member on which zinc plating, zinc alloy plating, or the like has been performed on a member composed of an iron-based material can be given. Even with such a substrate, using the chemical conversion treatment composition of the present embodiment, as described above, it is possible to appropriately perform the chemical conversion treatment for a long period of time.
[0065] Example
[0066] The following describes the effects of the present application based on examples, but the present application is not limited to them. A chemical conversion treatment composition containing an organic sulfur compound and capable of forming a black coating film was prepared so as to contain a phosphorus-containing compound including an organic phosphonic acid compound and to contain a vanadium-containing substance in a molar ratio of the molar concentration of vanadium to the molar concentration of a hydroxyl carboxylic acid-containing substance in the range of 1:0.5 to 1:10, and chemical conversion treatment was performed using the composition. The replenishment of the chemical conversion treatment composition was performed by quantitative replenishment, and the appearance change and the corrosion resistance change of the black coating film upon an increase in the cumulative treatment area were confirmed. Note that the chemical conversion treatment compositions used in the examples were all so-called hexavalent chromium-free compositions that substantially do not contain hexavalent chromium.
[0067] (1) Preparation of chemical conversion treatment composition
[0068] First, a chemical conversion treatment composition having the composition shown in Tables 1 to 3 was prepared. The pH thereof was adjusted to 2.4 using hydrochloric acid and sodium hydroxide. The values of chromium, nickel, and cobalt in the table are the contents of chromium, nickel, and cobalt in the chemical conversion treatment composition, respectively, in terms of chromium, nickel, and cobalt in the chromium-containing substance, the nickel-containing substance, and the cobalt-containing substance.
[0069] Further, in Table 4, as comparative examples, a chemical conversion treatment composition having the composition of Patent Literature 1 was prepared (Examples 19 to 26). Furthermore, in Table 5, as comparative examples, a chemical conversion treatment composition having the composition of Patent Literature 2 was prepared (Examples 27 and 28). The contents of the transition metals (nickel, vanadium, and manganese) used in the chemical conversion treatment compositions of Examples 20 to 27 were set to an intermediate value of 5 g / L, which is an intermediate value of the more preferable addition amount of 0.1 to 10 g / L described in Patent Literature 1.
[0070]
[0071]
[0072]
[0073]
[0074]
[0075] (2) Preparation of test member
[0076] Next, after the bolt subjected to electro-galvanizing by the conventional method was subjected to water washing, surface activation was performed by nitric acid immersion (3 mL / L of a solution of 67.5% nitric acid, liquid temperature: normal temperature (25°C), immersion time: 10 seconds). After the test member (substrate) was further subjected to water washing at normal temperature for 10 seconds, it was immersed in the chemical conversion treatment composition having the composition of Tables 1 to 3, and maintained at pH 2.4, 35°C for 45 seconds. After the test member was taken out of the chemical conversion treatment composition, it was subjected to water washing (normal temperature, 10 seconds), and then dried at 80 ± 5°C for 10 minutes.
[0077] Note that, for Examples 19 to 26 (comparative examples) shown in Table 4, the test member was immersed in the chemical conversion treatment composition maintained at pH 2.0, 30°C for 30 seconds, and for Examples 27 and 28 (comparative examples) shown in Table 5, the test member was immersed in the chemical conversion treatment composition maintained at pH 2.2, 35°C for 45 seconds. After the test member was taken out of the chemical conversion treatment composition, it was subjected to water washing (normal temperature, 10 seconds), and then dried at 80 ± 5°C for 10 minutes.
[0078] A plurality of bolts were subjected to surface treatment including the above chemical conversion treatment, and the test member obtained by the initial chemical conversion treatment after the bath was established, and the test member obtained by the chemical conversion treatment at a cumulative treatment area of 250, 500, 750, 1000 dm 2 per liter was used as the evaluation test member. Note that, at a cumulative treatment area of 500 dm 2 per liter, the concentration of zinc ions contained in the chemical conversion treatment composition was about 8 g / L, and at a cumulative treatment area of 1000 dm 2 per liter, the concentration of zinc ions contained in the chemical conversion treatment composition was about 15 g / L.
[0079] (3) Method of replenishment
[0080] As the chemical conversion treatment proceeds, the components of the chemical conversion treatment composition decrease, and therefore replenishment is performed at a rate of 100 dm 2 per liter of treatment area. The replenishment amount was determined as follows. First, when the treatment area reached 100 dm 2 per liter, the chemical conversion treatment composition was sampled, the chromium concentration was calculated by an ICP emission spectrometric analysis device ("ARCOS FH522" manufactured by SPECTRO), and the amount of chromium decrease in the sample was obtained. It was judged that each component of the chemical conversion treatment composition decreased at the same rate as the chromium decrease, and thus the amount of decrease of the chemical conversion treatment composition was calculated. As a specific example, if the treatment area per liter increased by 100 dm 2When the chromium reduction amount of the sample at the time is 10 mass%, it is judged that each component of the chemical conversion treatment composition is reduced by 10 mass%, and the composition having 1 / 10 amount of the chemical conversion treatment composition at the time of bath building is replenished.
[0081] (4) Evaluation method
[0082] The color tone was visually judged, and the corrosion resistance was evaluated by the salt spray test according to JIS Z2371. The presence or absence of white rust was visually confirmed every 24 hours, and when the white rust area ratio reached 5% of the whole, the cumulative salt spray time of the test member was set as the white rust occurrence time, and was used as an index of the corrosion resistance.
[0083] The evaluation results are shown in Tables 6 and 7. The appearance and corrosion resistance per 1 liter of cumulative treatment area are shown in the columns. As a specific example, a case where the time at which 5% of white rust occurred was 96 hours and the appearance at that time was black is indicated as "black / 96 hours".
[0084]
[0085]
Claims
1. A composition for chemical conversion treatment, characterized in that, contain: Substances containing trivalent chromium, organosulfur compounds, organophosphonic acid compounds, vanadium-containing substances, and substances containing hydroxycarboxylic acids.
2. The composition for chemical conversion treatment according to claim 1, wherein, The ratio of the molar concentration of the vanadium-containing substance (converted to vanadium) to the molar concentration of the hydroxycarboxylic acid-containing substance (converted to hydroxycarboxylic acid) is 1:1 to 1:
10.
3. The composition for chemical conversion treatment according to claim 1 or claim 2, wherein, The content of the trivalent chromium-containing substance is 1-10 g / L (converted to chromium), the content of the organosulfur compound is 0.1-10 g / L, and the content of the organophosphonic acid compound is 0.1-20 g / L.
4. The composition for chemical conversion treatment according to claim 1 or claim 2, wherein, contain: Choose one or more from the group consisting of nickel-containing substances and cobalt-containing substances.
5. The composition for chemical conversion treatment according to claim 1 or claim 2, wherein, contain: Zinc content is converted to a concentration of less than 15g / L.
6. A method for manufacturing a component with a chemical conversion coating, wherein, include: The chemical conversion treatment composition as described in claim 1 or claim 2 is brought into contact with a substrate having a surface containing zinc.
7. The manufacturing method according to claim 6, wherein, The chemical conversion treatment composition is managed through quantitative replenishment.
Citation Information
Patent Citations
JP1973040790A